Rape Culture, Gender Violence, and Religion Christian Perspectives (Religion and Radicalism, 2018)
This volume considers the complex relationships that exist between Christianity, rape culture, and gender violence. Each chapter explores the various roles that Christian theologies, teachings, and practices have played in shaping contemporary understandings of gender violence and in sanctioning rape-supportive cultural belief systems and practices. Our contributors explore this topic from a range of disciplinary perspectives, including theology, gender and queer studies, cultural studies, pastoral care, and counseling. Together, the chapters in this volume testify to the considerable influence that Christianity has had, and continues to have, in directing conversations within the Christian tradition around gender violence and rape culture. They therefore invite readers to engage fruitfully in these conversations, fostering transformative dialogues with the Christian community about our shared responsibility to tackle the current global crisis of gender violence. .